2016
DOI: 10.1007/s10461-016-1513-8
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Influence on HIV Testing Among Urban Men in Tanzania

Abstract: Men in sub-Saharan Africa have low HIV testing rates. Social networks exert an important influence on men’s HIV-related behavior. We examined associations between network factors and HIV testing among men in Dar es Salaam, Tanzania. Data are from the baseline assessment of an HIV prevention trial with 48 primarily male networks. Among 923 sexually active men, 52 % had ever tested for HIV. In a random effects logistic regression model, men in the network core were 1.50 times more likely (p <.05) to test than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 61 publications
3
57
1
Order By: Relevance
“…Since the 1990s, researchers have used social network data (e.g., partner notification and contact tracing) to understand sexual behavior (58) and epidemic change for both HIV (59,60) and other sexually transmitted infections (61). More recently, two approaches have been used to capture sexual networks de novo: (i) focusing on quasi-closed communities, such as those confined to islands (62) or those with well-defined social networks where boundary specification is relatively straightforward (63,64); and (ii) attempting to gain saturated coverage of behaviorally or geographically defined groups (65-68). One powerful emerging use of social networks for understanding HIV transmission is its combination with phylogenetic data, thereby attempting to minimize the limitations of both data types (69)(70)(71), although there remain important ethical issues to consider in such detailed inference (72).…”
Section: Using Social Network To Understand Hiv Treatment and Prevenmentioning
confidence: 99%
“…Since the 1990s, researchers have used social network data (e.g., partner notification and contact tracing) to understand sexual behavior (58) and epidemic change for both HIV (59,60) and other sexually transmitted infections (61). More recently, two approaches have been used to capture sexual networks de novo: (i) focusing on quasi-closed communities, such as those confined to islands (62) or those with well-defined social networks where boundary specification is relatively straightforward (63,64); and (ii) attempting to gain saturated coverage of behaviorally or geographically defined groups (65-68). One powerful emerging use of social networks for understanding HIV transmission is its combination with phylogenetic data, thereby attempting to minimize the limitations of both data types (69)(70)(71), although there remain important ethical issues to consider in such detailed inference (72).…”
Section: Using Social Network To Understand Hiv Treatment and Prevenmentioning
confidence: 99%
“…The main findings from this analysis vividly demonstrated that peer pressure (19) and opportunity cost of attending ANC instead of being at work (20) exerted significant influences on male partners and played major role in their decision to engage or attend antenatal care along with their pregnant partners. It was found that men as peers perceived themselves as a strong group hence did not see the need of listening to their partner.…”
Section: Discussionmentioning
confidence: 90%
“…We used a cluster design because we were interested in evaluating an intervention delivered within social networks [22]. Camp-based social networks serve as important socialization environments for men, propagating norms that are associated with men's sexual partner concurrency [23], IPV perpetration [24,25], as well as HIV testing [26,27].…”
Section: Methodsmentioning
confidence: 99%
“…The fact that men in camps engaged in the intervention and we were able to follow up with them over time suggests that camp-based networks are viable targets for interventions. The data we collected on these social networks provided us with important insight on how young men's social networks influence their HIV risk behaviors [25][26][27] and IPV [17].…”
Section: Plos Onementioning
confidence: 99%